Alum: an efficient catalyst for one-pot synthesis of alpha-aminophosphonates - Sonar, Swapnil S.; Shelke, Kiran F.; Kakade, Gopal K.; Shingate, Bapurao B.; Shingare, Murlidhar S. (Chinese Chemical Letters, 2009)
Alum (KAl(SO(4))(2)center dot 12H(2)O) is an inexpensive, efficient, non-toxic and mild catalyst for the one-pot synthesis of alpha-aminophosphonates. A three component reaction of an aldehyde/ketone, an an-tine and triethyl phosphite was carried out under solvent-free conditions to afford the corresponding alpha-aminophosphonates in short reaction times and high yields with the green aspects by avoiding toxic catalysts and solvents. (C) 2009 Murlidhar S. Shingare. Published by Elsevier B.V. on behalf of Chinese Chemical Society. All rights reserved.
Keywords: Aldehyde/ketone; alpha-Aminophosphonates; Alum; Amine; Solvent-free; Triethyl phosphite

Alum catalyzed convenient synthesis of quino [2,3-b][1,5]benzoxazepine alpha-aminophosphonate derivatives - Sonar, Swapnil S.; Sadaphal, Sandip A.; Shitole, Nana N.; Jogdand, Nivrutti R.; Shingate, Bapurao B.; Shingare, Murlidhar S. (Bulletin of the Korean Chemical Society, 2009)
We have described an efficient synthesis of quino[2,3-b][1,5]benzoxazepine alpha-aminophosphonate derivatives by the nucleophilic addition of triethyl phosphite to substituted quino[2,3-b][1,5]benzoxazepines promoted by easily available, inexpensive and mild catalyst KAl(SO(4))(2)center dot 12H(2)O (alum). The reactions proceed smoothly at room temperature under solvent-free reaction conditions and providing high yield of product in very short reaction time.
Keywords: 5]benzoxazepine; alpha-Aminophosphonate; Alum; Quino[2.3-b][1; Solvent-free; Triethyl phosphite

Ammonium metavanadate: an effective catalyst for synthesis of alpha-hydroxyphosphonates - Sonar, Swapnil S.; Kategaonkar, Amol H.; Ware, Madhav N.; Gill, Charansingh H.; Shingate, Bapurao B.; Shingare, Murlidhar S. (Arkivoc, 2009)
Ammonium metavanadate (NH(4)VO(3)) is an inexpensive, efficient and mild catalyst for the synthesis of alpha-hydroxyphosphonate derivatives by the reaction of various aryl or heteroaryl aldehydes with triethylphosphite at room temperature. This method affords the alpha-hydroxyphosphonates in short reaction times, under solvent-free conditions, and in high yield.
Keywords: Aldehyde; alpha-hydroxyphosphonate; Ammonium metavanadate (NH(4)VO(3)); Solvent-free; Triethyl phosphite

Amide-linked monocarbonyl curcumin analogues: efficient synthesis, antitubercular activity and molecular docking study - Subhedar, Dnyaneshwar D.; Shaikh, Mubarak H.; Nagargoje, Amol A.; Akolkar, V. Satish; Bhansali, Sujit G.; Sarkar, Dhiman; Shingate, Bapurao B. (Polycyclic Aromatic Compounds, 2022)
An approach toward the synthesis of novel conjugates of 3,5-bis (arylidene)-4-piperidones (DAP) pharmacophore with amide-linkage has been developed via one-pot multicomponent reaction of aryl aldehydes, piperidinone and 2-chloro-N-phenylacetamide using [Et3NH][HSO4] as a catalyst/medium. Both substitutions on arylidene rings and piperidinone nitrogen (substituted 2-chloro-N-phenylacetamide) were varied. The synthesized conjugates were evaluated for their in vitro antitubercular activity against M. tuberculosis H37Ra (MTB) and M. bovis BCG strains. Among the series, compounds 4f, 4g, 4i and 4j showed remarkable broad spectrum antitubercular activity with low IC50 values. Furthermore, computer docking simulations, for the most active conjugates were performed with the active site of mycobacterial enoyl-acyl carrier protein reductase (InhA) support the antitubercular activity. Lower cytotoxicity, high potency and promising activity against MTB and M. Bovis BCG suggest that amide linked DAP could serve as good leads for further modifications and development.
Keywords: antimycobacterial activity; Bis (arylidene)-4-piperidones; Cytotoxicity; Ionic liquid; Molecular docking Study